2016
DOI: 10.1088/0029-5515/57/1/016011
|View full text |Cite
|
Sign up to set email alerts
|

The physics and technology basis entering European system code studies for DEMO

Abstract: A large scale program to develop a conceptual design for a demonstration fusion power plant (DEMO) has been initiated in Europe. Central elements are the baseline design points, which are developed by system codes. The assessment of the credibility of these design points is often hampered by missing information. The main physics and technology content of the central European system codes have been published (Kovari et al 2014 Fusion Eng. Des. 89 3054–69, 2016 Fusion Eng. Des. 104 9–20, Reux et al 2015 Nucl. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 35 publications
3
111
0
1
Order By: Relevance
“…An allowable limit of the heat flux at the target for the DEMO reactor has been postulated to be below 5 MW m −2 , while the divertor plasma temperature should be below 5 eV to satisfy an acceptable erosion limit of the target. [8] However, P PLATE decreases below technical limits assumed for the DEMO tokamak, and the electron temperature at the outer plate is sustained above 5 eV. Profiles of the electron temperatures at the inner (left) and the outer (right) target plates are presented in Figure 3 for Γ Ne = 5.4 × 10 22 el s −1 and Γ Kr = 6.73 × 10 22 el s −1 in case of pure Ne and pure Kr seeding, respectively.…”
Section: Ne and Kr Seedingmentioning
confidence: 99%
“…An allowable limit of the heat flux at the target for the DEMO reactor has been postulated to be below 5 MW m −2 , while the divertor plasma temperature should be below 5 eV to satisfy an acceptable erosion limit of the target. [8] However, P PLATE decreases below technical limits assumed for the DEMO tokamak, and the electron temperature at the outer plate is sustained above 5 eV. Profiles of the electron temperatures at the inner (left) and the outer (right) target plates are presented in Figure 3 for Γ Ne = 5.4 × 10 22 el s −1 and Γ Kr = 6.73 × 10 22 el s −1 in case of pure Ne and pure Kr seeding, respectively.…”
Section: Ne and Kr Seedingmentioning
confidence: 99%
“…The simulation of a whole tokamak is a complex problem because it involves different phenomena and all subsystems are not entirely independent from each other. In order to understand and design a whole fusion plant, a fast and reliable simulation code is inevitable [6,7]. The SYCOMORE code is a modular system code which aims at modelling future fusion power plants with all subsystems and to provide a global view of the whole plant [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The actual model of a DEMO divertor segment with the pumping port to be positioned at the bottom of the middle cassette is shown in Fig.1. The depicted divertor configuration is based on the 2015 EU DEMO baseline design [4], which consists of 54 divertor cassettes in total and has a major radius R=9.1 m. The presented configuration has been compared with the latest 2017 DEMO divertor design and no significant geometrical discrepancies, which may influence the outcome of this study, has been observed. Due to toroidal symmetry we consider only one sector of 20°, which includes 3 divertor cassettes without the dome structure, two poloidal gaps between the cassettes (i.e inter-cassette gaps) and two toroidal gaps between the first wall and the divertor cassettes in both the low field and high field sides (LFS and HFS).…”
Section: Introductionmentioning
confidence: 99%